Applying Evidence-Centered Design for the Development of Game-Based Assessments in Physics Playground. Issue 2 (2nd April 2016) - Kim, Yoon Jeon; Almond, Russell G.; Shute, Valerie J.
Abstract : Game-based assessment (GBA) is a specific use of educational games that employs game activities to elicit evidence for educationally valuable skills and knowledge. While this approach can provide individualized and diagnostic information about students, the design and development of assessment mechanics for a GBA is a nontrivial task. In this article, we describe the 10-step procedure that the design team of Physics Playground (formerly known as Newton's Playground ) has established by adapting evidence-centered design to address unique challenges of GBA. The scaling method used for Physics Playground was Bayesian networks; thus this article describes specific actions taken for the iterative process of constructing and revising Bayesian networks in the context of the game Physics Playground.